2023
DOI: 10.3847/1538-4357/acb26a
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency Decayless Waves with Significant Energy in Solar Orbiter/EUI Observations

Abstract: High-frequency wave phenomena present a great deal of interest as one of the possible candidates to contribute to the energy input required to heat the corona as a part of the alternating current heating theory. However, the resolution of imaging instruments up until the Solar Orbiter has made it impossible to resolve the necessary time and spatial scales. The present paper reports on high-frequency transverse motions in a small loop located in a quiet-Sun region of the corona. The oscillations were observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 51 publications
2
7
1
Order By: Relevance
“…The oscillation period is 1-8 minutes while the loop length ranges from 14 to 42 Mm. Unlike previous observations (Anfinogentov et al 2015;Li & Long 2023;Petrova et al 2023), no obvious linear correlation was found between the oscillation period and loop length. Meanwhile, the distribution of the period shows a peak at about 5 minutes (see Figure 3 in Gao et al 2022a).…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The oscillation period is 1-8 minutes while the loop length ranges from 14 to 42 Mm. Unlike previous observations (Anfinogentov et al 2015;Li & Long 2023;Petrova et al 2023), no obvious linear correlation was found between the oscillation period and loop length. Meanwhile, the distribution of the period shows a peak at about 5 minutes (see Figure 3 in Gao et al 2022a).…”
Section: Introductioncontrasting
confidence: 99%
“…Recently, decayless oscillations have also been found in short coronal loops (50 Mm) with the high-resolution 174 A  images taken by the Extreme Ultraviolet Imager (EUI; Rochus et al 2020) on board the Solar Orbiter (SolO; Müller et al 2020). Petrova et al (2023) reported high-frequency oscillations in two coronal loops with lengths of 4.5 Mm and 11 Mm located in a quiet-Sun region. The measured periods are 14 and 30 s, much shorter than in longer coronal loops.…”
Section: Introductionmentioning
confidence: 97%
“…The literature with details is summarized in Table 1. We need to note that among the oscillations we consider, while there are cases where the decayless oscillations were clearly identified as standing modes, there are cases where the interpretation of whether observed oscillations are standing or propagating waves still remains open (Gao et al 2022;Petrova et al 2023;Shrivastav et al 2023). In this study, all decayless oscillations we consider in this study are assumed to be standing modes.…”
Section: Energy Property Distributionsmentioning
confidence: 99%
“…The discovery of rapid decayless oscillations in smaller loop structures, which had not been observed due to the limitations of AIA's time cadence and spatial resolution, has been accelerated by the unprecedented high spatial and temporal resolution of the High Resolution Imager (HRI) of the Extreme Ultraviolet Imager (EUI; Rochus et al 2020) aboard the Solar Orbiter (SolO; Müller et al 2020). Petrova et al (2023) first discovered high-frequency transverse oscillations with periods of 30 and 14 s. Zhong et al (2022b) presented short-period (1-3 minutes) decayless oscillations simultaneously observed in both SolO/EUI and SDO/AIA for the first time. As the oscillation results in EUI and AIA are consistent with each other, it confirmed that the observations of high-frequency oscillations by EUI are robust.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation